Peak displacement demand of small to moderate magnitude earthquakes in stable continental regions. - Lam, Nelson
A theoretical fault slip model has been developed for predicting the notional peak displacement demand (PDD) of earthquakes based on a limiting natural period of 5 s, for application in stable continental region (SCRs). The developed theoretical expression is simple and robust. Importantly, it envelops predictions arising from a number of existing empirical and seismological (stochastic) models included in the comparison. The notional PDD prediction has been made initially for hard rock crustal conditions and at a reference source-site distance of 30 km. Factors have accordingly been introduced to correct for different distances and geological conditions in completing the PDD prediction model. Assuming displacement controlled behavior, the predicted notional PDD may be compared with the displacement capacity of a structure, or component, for purposes of seismic stability assessment.
Keywords: Earthquake; Notional peak displacement demand; Displacement based approach; Response spectrum; Component attenuation model; Seismic drift